THE EFFECT OF 8-WEEK PLYOMETRIC TRAINING ON LEG POWER, JUMP AND SPRINT PERFORMANCE IN FEMALE SOCCER PLAYERS - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2014)
Ozbar, N, Ates, S, and Agopyan, A. The effect of 8-week plyometric training on leg power, jump and sprint performance in female soccer players. J Strength Cond Res 28(10): 2888-2894, 2014The aim of this study was to determine the effect of 8-week plyometric training (PT) on the leg power and jump and sprint performance in female soccer players. Eighteen female soccer players from Women Second League (age = 18.2 +/- 2.3 years, height = 161.3 +/- 5.4 cm, body mass = 56.6 +/- 7.2 kg) were randomly assigned to control (n = 9) and plyometric (n = 9) groups. Both groups continued together with regular technical and tactical soccer training for 4 days a week. Additionally, the plyometric group underwent PT for 8 weeks, 1 day per week, 60-minute session duration. During the 8-week period, the control group was hindered from any additional conditioning training. All players' jumps (triple hop, countermovement jump, and standing broad jump), running speed (20 m), and peak power were evaluated before and after 8 weeks. No significant difference was found between the groups at pretest variables (p > 0.05). Significant improvements were found in the posttest of both the groups (p 0.05), except for 20-m sprint test in the control group (p > 0.05). Triple hop distance, countermovement jump, standing broad jump, peak power, and 20-m sprint test values were all significantly improved in the plyometric group, compared with the control group (p 0.05). We concluded that short duration PT is an improved important component of athletic performance in female soccer players. The results indicate that safe, effective, and alternative PT can be useful to strength and conditioning coaches, especially during competition season where less time is available for training.
Keywords: stretch-shortening cycle; lower limb; jumping ability; running speed; football; explosive power; VERTICAL JUMP; IN-SEASON; STRENGTH; PROGRAM; METAANALYSIS; EXERCISES; ENDURANCE; CAPACITY; AGILITY; HEIGHT